2020
DOI: 10.1080/07391102.2020.1850359
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic flavonoids as potential antiviral agents against SARS-CoV-2 main protease

Abstract: The COVID-19 pandemic has claimed more than a million lives worldwide within a short time span. Due to the unavailability of specific antiviral drugs or vaccine, the infections are causing panic both in general public and among healthcare providers. Therefore, an urgent discovery and development of effective antiviral drug for the treatment of COVID-19 is highly desired. Targeting the main protease (M pro) of the causative agent, SARS-CoV-2 has great potential for drug discovery and drug repurposing efforts. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Several studies have reported that rutin, a flavonol glycoside, has high efficacy as a potent inhibitor to treat COVID-19 infection and noncovalent interact with the heteroatoms of amino acids of the M pro ’s active sit ( Ibrahim et al, 2021 ). Batool et a l identified TF-9, a thioflavonol, as a highly promising inhibitor of SARS-CoV-2 M pro with predicted binding energy of -8.7 kcal/mol from 101 synthetic flavonols ( Batool et al, 2020 ). Quercetin was identified as reasonably potent inhibitor of SARS-CoV-2 3CLpro with Ki∼7 μM from a small chemical library ( Abian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that rutin, a flavonol glycoside, has high efficacy as a potent inhibitor to treat COVID-19 infection and noncovalent interact with the heteroatoms of amino acids of the M pro ’s active sit ( Ibrahim et al, 2021 ). Batool et a l identified TF-9, a thioflavonol, as a highly promising inhibitor of SARS-CoV-2 M pro with predicted binding energy of -8.7 kcal/mol from 101 synthetic flavonols ( Batool et al, 2020 ). Quercetin was identified as reasonably potent inhibitor of SARS-CoV-2 3CLpro with Ki∼7 μM from a small chemical library ( Abian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arbutin, terbutaline, barnidipine, tipiracil, and aprepitant were identified as potential hits forming different hydrophilic, hydrophobic, and electrostatic interactions with M pro ( Baby et al, 2020 ). Thioflavonol is a synthetic flavonoid analog that showed a strong binding with the conserved residues in the S1 subsite ( Batool et al, 2020 ).…”
Section: Potential Inhibitors Of Sars-cov-2 M Promentioning
confidence: 99%
“…Fayyaz et al screened several flavonoids and identified three potentially active flavonoids, whose activities against SARS-CoV-2 M pro were in the order of rhodiolin > baicalin > silymarin based on their binding energy (−9.05, −8.85, −8.71 kcal/mol respectively) and dissociation constant (0.23, 0.33, 0.41 µm, respectively) using molecular docking and simulation studies [147]. Thioflavonol also inhibits Mpro [148] along with other flavonoids such as apigenin, daidzein, quercetin, kaempferol, luteolin, epigallocatechin, and kaempferol using molecular docking and simulation analysis [104].…”
Section: Flavonoids Against Sars-cov-2 M Promentioning
confidence: 99%